A framework to collect human reliability analysis data for nuclear power plants using a simplified simulator and student operators. (May 2022) - Park, Jooyoung; Boring, Ronald L.; Ulrich, Thomas A.; Lew, Roger; Lee, Sungheon; Park, Bumjun; Kim, Jonghyun
Highlights: The Simplified Human Error Experimental Program (SHEEP) framework is proposed. SHEEP aims to collect HRA data using simplified simulators and student operators. The differences between student and professional operators using a simplified simulator are investigated. The use of SHEEP data to support HuREX data collection is explored. Abstract: Data scarcity in human reliability analysis (HRA) has been a major challenge in the quantification process. Many institutes have collected HRA data through experiments using full-scope simulators with actual operators. Nevertheless, there are still some limitations to relying solely on full-scope studies. This paper aims to propose how full-scope data collection studies can be supported through the Simplified Human Error Experimental Program (SHEEP). The SHEEP framework was developed by Idaho National Laboratory (INL) to collect HRA data through a simplified simulator and student operators. This paper introduces the major tasks in the SHEEP framework, with a particular focus on differences that arise due to participant type (i.e., student vs. actual operator), based on experiments using a simplified simulator (i.e., the Rancor Microworld). This paper also describes whether the data collected via this approach could support a representative full-scope data collection study (i.e., the HuREX study) based on the experimental data.